ICT-projects-modeling based experience for teaching of systems of differential equations - Molina-Mora, Jose-Arturo (2015)
One of the challenges in education is the continuous improvement in order to search for new strategies in the management of teaching and learning and the quality of the process. The incorporation of ICTs (Information and Communication), project teaching and mathematical modeling propose a strategy for teaching of systems of differential equations at the university level. The implementation showed favorable results on the students, who had to schematically describe the problem, raise the mathematical model, perform and analyze simulations and predictions, in all cases with problems related to the student's academic area.